Technological characteristics of cataract surgery in eyes with posterior chamber phakic intraocular lens implanted previously (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Implantation of phakic intraocular lenses (PIOL) is used for the correction of high myopia. The problem of PIOL implantation is that cataract may develop in a long-term period after surgery due to the contact of constructive PIOL elements to anterior and posterior chamber tissues. So, the development of advanced surgical techniques enabling to perform bilensectomy as safely and quickly as possible is of a great importance.The purpose of the present study was to improve the technique for cataract extraction in patients with posterior chamber PIOLs implanted previously.Material and Methods. A total of 19 cases of cataract extraction in 11 patients with plus and minus models of posterior chamber PIOLs were studied. 12 of explanted PIOLs were made of collagen copolymer and 7 of them were of silicone.Results. Endothelial cell loss (ECL) after bilensectomy averaged 9.1% in a study group. ECL increased after cataract phaco emulsification to 11% in 11 eyes at time point of 6 months after surgery and to 12.2% in 5 eyes with five-year follow-up.There was noted a tendency of a more rapid visual function recovery (on the average, at Day 5 after surgery) and less endothelial cell loss when using the bilensectomy techniques improved. Conclusion. The improved bilensectomy technique enabled to perform effectively and safely the rehabilitation of patients with cataract with implanted PIOLs.
Keywords: cataract; phakic intraocular lens; bilensectomy